2022
DOI: 10.1038/s41598-022-15225-3
|View full text |Cite
|
Sign up to set email alerts
|

A structural homology approach to identify potential cross-reactive antibody responses following SARS-CoV-2 infection

Abstract: The emergence of the novel SARS-CoV-2 virus is the most important public-health issue of our time. Understanding the diverse clinical presentations of the ensuing disease, COVID-19, remains a critical unmet need. Here we present a comprehensive listing of the diverse clinical indications associated with COVID-19. We explore the theory that anti-SARS-CoV-2 antibodies could cross-react with endogenous human proteins driving some of the pathologies associated with COVID-19. We describe a novel computational appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…4 It is reported that some anti-SARS-CoV-2 spike antibodies react with the myosin-containing human protein structure. 5 This hypothesis may also be persuasive in our case because the pathogenic T cells activated in the SARS-CoV-2 mRNA infection could behave as inducers of SARS-CoV-2 mRNA vaccine-associated myocarditis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…4 It is reported that some anti-SARS-CoV-2 spike antibodies react with the myosin-containing human protein structure. 5 This hypothesis may also be persuasive in our case because the pathogenic T cells activated in the SARS-CoV-2 mRNA infection could behave as inducers of SARS-CoV-2 mRNA vaccine-associated myocarditis.…”
Section: Discussionmentioning
confidence: 68%
“…Molecular mimicry between the spike protein antigen and autologous cardiac antigen has been postulated as one of the mechanisms of SARS‐CoV‐2 mRNA vaccine‐associated myocarditis 4 . It is reported that some anti‐SARS‐CoV‐2 spike antibodies react with the myosin‐containing human protein structure 5 . This hypothesis may also be persuasive in our case because the pathogenic T cells activated in the SARS‐CoV‐2 mRNA infection could behave as inducers of SARS‐CoV‐2 mRNA vaccine‐associated myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by JR McGill et al (2022) (25), which was conducted with the aim of identifying antibody responses and potential antibody reactions in COVID-19 patients, It appears that anti-SARS-CoV-2 antibodies can cross-react with endogenous human proteins that drive some of the pathologies associated with COVID-19. In line with the results of our study, the results of this study showed that the anti-catenin antibody has high reactivity in COVID-19 patients and can play a significant role in the process of pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…При картировании антигенных эпитопов выявлена гомология между компонентами SARS-CoV-2 (S-белок, нуклеопротеин) и тканевыми антигенами, включая митохондрии M2, F-актин, тропонин и др. При изучении структурной гомологии между белками SARS-CoV-2 и белками человека с использованием расчетного (computational) метода идентифицировано 346 белков, содержащих домены с высокой структурной гомологией с белком SARS-CoV-2, среди которых 102 белка обладали функциональной активностью, потенциально участвующей в патогенезе COVID-19 [120].…”
Section: аутоантителаunclassified